ApoE isoform does not influence skeletal muscle regeneration in adult mice - Burke, Benjamin I.; Goh, Jensen; Albathi, Fatmah A.; Valentino, Taylor R.; Nolt, Georgia L.; Joshi, Jai K.; Dungan, Cory M.; Johnson, Lance A.; Wen, Yuan; Ismaeel, Ahmed; McCarthy, John J. (Frontiers in Physiology, 2023)
Apolipoprotein E (ApoE) has been shown to be necessary for proper skeletal muscle regeneration. Consistent with this finding, single-cell RNA-sequencing analyses of skeletal muscle stem cells (MuSCs) revealed that Apoe is a top marker of quiescent MuSCs that is down-regulated upon activation. The purpose of this study was to determine if muscle regeneration is altered in mice which harbor one of the three common human ApoE isoforms, referred to as ApoE2, E3 and E4. There was no difference in the basal skeletal muscle phenotype of ApoE isoforms as evaluated by section area, myofiber cross-sectional area (CSA), and myonuclear and MuSC abundance per fiber. Although there were no differences in fiber-type frequency in the soleus, Type IIa relative frequency was significantly lower in plantaris muscles of ApoE4 mice compared to ApoE3. Moreover, ApoE isoform did not influence muscle regeneration after 14 days of recovery from barium chlorideinduced muscle damage as assessed by fiber frequency, fiber CSA, and myonuclear and MuSC abundance. Finally, there were no differences in the proliferative capacity or myogenic 2 This is a provisional file, not the final typeset article differentiation potential of MuSCs between any ApoE isoform. Collectively, these data indicate nominal effects of ApoE isoform on the ability of skeletal muscle to regenerate following injury or the in vitro MuSC phenotype.